Development of android application-based physics learning media to enhance high school students' higher-order thinking skills - Priatna, Rapi; Agustina, Tri Wahyu; Malik, Adam (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
The purpose of this study is to examine the development process and feasibility of Android application-based physics learning media, the implementation of learning activities, and the improvement of students' higher-order thinking skills. The research method used in this study is research and development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The sample consisted of 36 eleventh-grade students from a public high school in Bandung Regency. The results of the study indicate that the developed Android application-based physics learning media is highly feasible, achieving an average validation and small-scale trial score of 86%. Learning activities were effectively implemented, with an average percentage of teacher activities reaching 93% and student activities 90%. Hypothesis testing using a paired sample t-test at a significance level of 0.05 resulted in a calculated t-value of 43.135, compared to a critical t-value of 2.0345. It can thus be concluded that students' higher-order thinking skills improved significantly after learning through the Android application-based physics learning media on the topic of mechanical waves, with an N-gain score of 0.74.